2020
DOI: 10.31413/nativa.v8i1.8130
|View full text |Cite
|
Sign up to set email alerts
|

Análise Multicritério Na Definição De Áreas Prioritárias Para Recuperação Florestal Na Bacia Do Rio Doce, Em Minas Gerais

Abstract: A Floresta Atlântica é um dos ecossistemas mais fragmentado e explorado. Como atividades de restauração florestal são dispendiosas, a Análise de Decisão Multicritério (ADMC) integrada ao SIG (Sistema de Informações Geográficas) fornece um satisfatório suporte de decisão espacial para produção de mapas de forma eficiente. O colapso de uma barragem de mineração em áreas de floresta Atlântica, resultou na destruição de comunidades por rejeitos de mineração na bacia hidrográfica do Rio Doce. Assim, o objetivo dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In this study, Silva et al concluded that AMC was efficient for determining priority areas in watersheds and could be a great management tool. Almeida et al (2020) performed an AMC to define priority areas for forest recovery in the Rio Doce watershed using factors such as proximity to forest remnants, water bodies, and slope. Almeida et al concluded that multicriteria analysis was an easy-to-implement and efficient tool, where, provided that the database was solid, it was possible to obtain maps that helped in predicting adequate solutions with the aim of recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Silva et al concluded that AMC was efficient for determining priority areas in watersheds and could be a great management tool. Almeida et al (2020) performed an AMC to define priority areas for forest recovery in the Rio Doce watershed using factors such as proximity to forest remnants, water bodies, and slope. Almeida et al concluded that multicriteria analysis was an easy-to-implement and efficient tool, where, provided that the database was solid, it was possible to obtain maps that helped in predicting adequate solutions with the aim of recovery.…”
Section: Resultsmentioning
confidence: 99%
“…This comparison is based on a scale recommended by Saaty (1990; Table 1), where values greater than 1 have a greater degree of importance, values less than 1 represent a lesser degree of importance, and values equal to 1 have equal importance. Thus, the AHP method allows associating relative weights, in order of priority, to distinguish the importance that each criterion will have for decision‐making (Almeida et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In Figure 5 it is possible to visualize the flowchart containing the methodological steps used to delimit the priority areas for forest recovery. The weights for each IP were also defined, according to [37] (Frame 5). The slope map was made from the Slope tool, using the DEM of the Itapemirim river basin, where it was subsequently reclassified into their respective classes.…”
Section: Forest Fragments Costsmentioning
confidence: 99%
“…AHP is a quantitative method used to prioritize decision alternatives and select an alternative that satisfies pre-defined criteria (SAATY, 2008). AHP has been applied in various studies related to environmental fragility (FRANÇA et al, 2019), mapping and identifying priority areas for forest recovery (DE ALMEIDA et al, 2020), food security under climate change (ALLIPOUR BIRGANI et al, 2022), and groundwater management under climate change (SCHEIHING et al, 2022). To assess the impact of climate change on different types of agricultural production, this study combines AHP with the calculation of climate change impact indices following the formula by Balica and Wright (BALICA & WRIGHT, 2010;TÍN et al, 2018) and classifies the degree of climate change impact according to Le Anh Tuan (LE et al, 2013).…”
Section: Analytic Hierarchy Process (Ahp)mentioning
confidence: 99%